Outcomes of patients with acute myeloid leukemia and bone marrow fibrosis - Samuel Urrutia; Hagop M. Kantarjian; Farhad Ravandi-Kashani; Carlos Bueso-Ramos; Rashmi Kanagal-Shamanna; Elias Jabbour; Guillermo Montalban-Bravo; Nicholas J. Short; Naval Daver; Gautam Borthakur; Courtney D. Dinardo; Tapan M. Kadia; et al. (Journal of Hematology & Oncology)
Abstract The outcomes of patients with acute myeloid leukemia (AML) and bone marrow fibrosis (MF) are not well defined. The study objectives were to evaluate the degrees of MF in AML, and corresponding response rates and outcomes. We performed a retrospective review of 2302 patients with AML. We annotated the clinical and molecular characteristics, response to therapy, and survival outcomes of patients with bone marrow fibrosis. Overall, 492 patients (21.4%) had a reported microscopic evaluation of MF: 344 (69.9%) had MF grade 0–1 and 148 (30.1%) had MF grade 2–3. Patients with MF 2–3 had a higher proportion of complex cytogenetics (39.2% vs. 24.7%, p = 0.002) JAK2 mutations (25.7% vs. 18%, p = 0.07) and lower proportion of IDH2 (16.9% vs. 25.9%, p = 0.03) and CEBPA (15.5% vs. 27.6%, p = 0.006) mutations. 64% were treated with low-intensity chemotherapy (LIT) and 36.1% with intensive chemotherapy (IT). The complete remission (CR)/CR with incomplete count recovery (CRi) rates were 63.5% with IC versus 37.9% with LIT (p = 0.007). In patients aged 60 or older 4-week mortality was 12.5% with IC vs. 9.3% with LIT (p = 0.8). The median overall survival (OS) was 14.2 with MF 0–1 versus 7.5 months with MF 2–3 (p < 0.005). In patients aged 60 or older with MF 2–3 median OS was 6.5 months with IT versus 7.0 months with LIT (p = 0.19). In a multivariate analysis, grade 2–3 MF (HR 2.0, 95%CI 1.59–2.51) was the strongest prognostic factor for survival. In summary, grade 2–3 MF in AML is associated with worse outcomes.